Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Discovery Learning pada Materi Hukum Newton untuk Meningkatkan Pemahaman Konsep Siswa - Batdratun Napis; Muliani Muliani; Fajrul Wahdi Ginting; Nanda Novita; Widya Widya (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Learner Worksheet (LKPD) is one type of teaching media that is used as a guide for students to make it easier for students to understand the subject matter being studied. The learning process at MAN 3 Aceh Timur currently still uses a conventional model and teachers have not conducted learning using interactive teaching media such as LKPD. This study aims to determine the feasibility, response and improvement of concept understanding by developing and applying LKPD in the learning process. This development research method refers to Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, evaluation), the research subject is class X MIA with 14 students as the experimental class and class X IIK with 14 students as the control class and the object of research located at MAN 3 Aceh Timur. The results obtained: 1) the results of the validation of media experts with the category “very feasible” while the results of the validation of material experts with the category “very feasible”, 2) The results of teacher responses in the “very practical” category and the results of student responses in the “very practical” category, 3) N-Gain test conducted in class X MIA (experimental) obtained a result of 0.60 with a percentage of 60% in the “medium” category. The results of this study indicate that the discovery learning-based LKPD learning media developed is feasible to use and can improve students' concept understanding.